Squire - Pierce, Tamora (Pierce, Tamora. Protector of the small., 2001)
After becoming a squire to Lord Raoul, commander of the King's Own, Kel of Mindelan, must face a terrifying test in the Chamber of the Ordeal before she can be a knight.